กระบวนการถ่ายทอดความรู้ของครอบครัวทำแคน : กรณีศึกษา บ้านสีแก้ว ตำบลสีแก้ว อำเภอเมือง จังหวัดร้อยเอ็ด Process knowledge transfer of Kaen Making Family : A Cast Study of Sikaeo Village Tambon Sikaeo Muang District Roi-et Province - พันธะศรี พิทยวัฒน์; นามสง่า ปริยัติ (Chophayom Journal, 2017)
บทคัดย่อ การศึกษากระบวนการถ่ายทอดความรู้ของครอบครัวทำแคน : กรณีศึกษา บ้านสีแก้ว ตำบลสีแก้ว อำเภอเมือง จังหวัดร้อยเอ็ด มีวัตถุประสงค์ดังนี้ 1. ศึกษาวัสดุ อุปกรณ์ และวิธีการผลิตแคนของชาวบ้านสีแก้ว ตำบลสีแก้ว อำเภอเมือง จังหวัดร้อยเอ็ด 2. ศึกษากระบวนการถ่ายทอดภูมิปัญญาการผลิตแคนของชาวบ้านสีแก้ว ตำบลสีแก้ว อำเภอเมือง จังหวัดร้อยเอ็ดโดยการเก็บรวบรวมข้อมูลจากเอกสาร การสังเกต การสัมภาษณ์เชิงลึก โดยใช้ระเบียบวิธีวิจัยเชิงคุณภาพในการเก็บรวบรวมข้อมูลและวิเคราะห์ข้อมูลแบบพรรณนาวิเคราะห์ตั้งแต่เดือนตุลาคม 2558 – มกราคม 2560 ซึ่งผลการศึกษาสรุปได้ ดังนี้ ผลการวิจัยพบว่า วัสดุที่ใช้ทำแคนประกอบด้วย ไม้ไผ่เฮี้ยรากไม้ประดู่ ขี้สูด หลาบโลหะไม้คั่น เครือหญ้านาง ปูนขาวอุปกรณ์เครื่องมือของช่างทำแคนประกอบด้วย มีดตอก มีดโต้เหล็กซีสิ่วเจาะ สิ่วกานทองสิ่วสับค้อน ทั่งกรรไกรเหล็กแซ้นติวไม้ชาไม้มือลิง เลื่อย หินลับมีด ส่วนขั้นตอนการผลิตแคน ประกอบด้วย การเตรียมลำลูกแคนการผลิตลิ้นแคนการติดตั้งลิ้นแคนการทำเต้าแคนการผนึกลูกแคนเข้าเต้าแคนการผูกมัดแพลูกแคนการเจาะรูนับเสียงโดยระบบเสียงแคนแปดจากเสียงที่ 1 ถึงเสียงที่ 7 ประกอบด้วยเสียง F#, G# , A, B, C# , D, E,เสียงฟาชาร์ปเนเจอรัลไมเนอร์สเกล (F#Natural minor Scale) กระบวนการถ่ายทอดภูมิปัญญาการผลิตแคนประกอบด้วย การถ่ายทอดโดยวิธีการมุขปาฐะการถ่ายทอดโดยการสาธิตการถ่ายทอดโดยใช้สื่อการสอนการถ่ายทอดโดยการปฏิบัติตามคำบอกการถ่ายทอดโดยเน้นการจำเป็นหลักการถ่ายทอดโดยให้ผู้เรียนได้รับประสบการณ์จริง แม้ปัจจุบันช่างทำแคนบ้านสีแก้วจะไม่สามารถยึดอาชีพทำแคนเป็นอาชีพหลักได้ เพราะไม่สามารถพัฒนาผลิตภัณฑ์และการตลาด รวมทั้งความต้องการของผู้บริโภคก็เป็นเพียงกลุ่มน้อย ปัจจุบันจึงยังใช้รูปแบบการผลิตตามคำสั่งซื้อของลูกค้าอยู่ แต่ถึงกระนั้นอาชีพช่างทำแคนก็ยังคงเป็นที่ต้องการของสังคม โดยเฉพาะช่างบ้านสีแก้วที่มีประวัติการทำแคนที่ยาวนาน อีกทั้งวัฒนธรรมหมอลำหมอแคนยังคงอยู่คู่กับชาวอีสาน ช่างทำแคนจึงยังต้องรักษาหน้าที่นี้ในสังคมต่อไป คำสำคัญ : แคน กระบวนการถ่ายทอด บ้านสีแก้ว จังหวัดร้อยเอ็ด ABSTRACT The study of knowledge transfer in Kaen making families case studied in Sikaeo Village Tambon Sikaeo, Muang District, Roi-et Province could be one of methods used to conserve local wisdoms in the area. The current study was conducted to investigate two main issues which were 1) materials, tools, and manufacturing processes used in the produce of kaen, a North-eastern Thailand traditional music instrument and 2) processes in knowledge transfer of the instrument in Sikaeo Village, Tambon Sikaeo, Muang District, Roi-et Province. The data were collected by using document analysis, observation, and in-depth interview. The data were analyzed by the qualitative approach and gathered from October 2015 to January 2017. The results of the study showed that the materials used in the manufacture of Kean included bamboo, pradu’s root (Pterocarpusmacrocarpus), Trigona germ, slim brass plate, dividing latch, Ya Nang (Tiliacoratriandra) vine, and lime. Moreover, tools used in the manufacturing processes included knives, hole punchers, chisels, gouges, v-gouges, hammers, anvils, scissors, bending tools, rasps, saws, and sharpening stones. In terms of processes of manufacturing, the processes included preparation of kean pipes, production of kaen tongue, the tongue set up, production of the blowing part, pipes and blowing part set up, pipe tiding, and melodic hole putting. In detail, a kean could produce seven sounds including F#, G# , A, B, C# , D, and E respectively in F# natural minor Scale. In terms of knowledge transfer processes of Kaen making family, it was found that oral instruction, demonstration, multimedia, listening and practice, and memory focused instruction were used as the main principles in knowledge transfer. In the present situation, kaen makers in the area, unfortunately, could not rely on kaen production as the main occupation as they could not develop the products to reach marketing needs and the market of kaen is considered too narrow. The production, therefore; depends on individual orders. However, kean maker, especially skilled one, remains an important career in the society since Moh-lum is still demanded as the popular entertaining performance in Isan area. Consequently, kaen makers could still have their place in the society. Keywords : Kaen, knowledge transfer, Sikaeo Village, Roi-Ed province